Making the best better: performance psychology integrated in special operation forces training - Ytterbøl, Christian; Collins, Dave; MacPherson, Alan (Frontiers in Psychology, 2025)
IntroductionThis study investigates how performance psychology was employed in conjunction with an operational combat squadron in NORSOF (Norwegian Special Operation Forces) whilst they were preparing for deployment. Access to this group allowed the research team to evaluate the contribution which a performance psychology package (PP) can make to an elite military unit with little or no previous exposure of such training.MethodsThe study utilized an explorative longitudinal case study format to evaluate a mixed intervention. Content was delivered in two formats: psychoeducation in a classroom setting and in situ PP delivery during training. Data were collected through four stages of semi-structured, in-depth interviews with a significant time interval between each stage. Stage one occurred prior to the intervention—offering an informal baseline to understand what knowledge and skills the operators perceived in themselves; Stage two was conducted prior to deployment, after the unit's workup had finished. Stage three data was gathered upon the unit's return from deployment. Finally, as stage 4, an 18-month follow-up was conducted with key members of the unit.ResultsAnalyzed through Reflective Thematic Analysis, results indicate that the operators already held a high level of mental skills—likely a result of absorbing practices that are learned and developed in order to adapt successfully to their performance environment. Importantly, however, results also indicate that the additional structured PP intervention, integrated within the unit's workup training, increased perceived performance at both an individual and unit level. The follow-up supports the initial results. Discussion: Although SOF already are high performers and very good at what they do, our contention is that performance psychology could be a valuable and important concept to integrate and develop further.